Skip to content
Related Articles

Related Articles

Improve Article

Class 9 RD Sharma Solutions – Chapter 6 Factorisation of Polynomials- Exercise 6.5 | Set 2

  • Last Updated : 30 Apr, 2021
Geek Week

Question 11. Using factor theorem, factorize of the polynomials : x3 – 10x2 – 53x – 42

Solution:

Given that,

f(x) = x3–10x2 – 53x – 42

The constant in f(x) is – 42,

The factors of – 42 are ± 1, ± 2, ± 3, ± 6, ± 7, ± 14, ± 21,± 42,



Let’s assume, x + 1 = 0

x = – 1

f(-1) = (−1)3 –10(−1)2 – 53(−1) – 42

-1 – 10 + 53 – 42 = 0

therefore, (x + 1) is the factor of f(x)

Now, divide f(x) with (x + 1) to get other factors

By using long division method we get,

x3 – 10x2 – 53x – 42 = (x + 1) (x2 – 11x – 42)

Now,

x2 – 11x – 42 = x2 – 14x + 3x – 42

x(x – 14) + 3(x – 14)

(x + 3)(x – 14)

Hence, x3 – 10x2 – 53x – 42 = (x + 1) (x + 3)(x – 14)

Question 12. Using factor theorem, factorize of the polynomials : y3 – 2y2 – 29y – 42

Solution:

Given that, f(x) = y3 – 2y2 – 29y – 42

The constant in f(x) is – 42,

The factors of -42 are ± 1, ± 2, ± 3, ± 6, ± 7, ± 14, ± 21,± 42,

Let’s assume, y + 2 = 0



y = – 2

f(-2) =  (−2)3 – 2(−2)2–29(−2) – 42

-8 -8 + 58 – 42 = 0

therefore, (y + 2) is the factor of f(y)

Now, divide f(y) with (y + 2) to get other factors

By using long division method we get,

y3 – 2y2 – 29y – 42 = (y + 2) (y2 – 4y – 21)

Now,

y2 – 4y – 21 = y2 – 7y + 3y – 21

y(y – 7) +3(y – 7)

(y – 7)(y + 3)

Hence, y3 – 2y2 – 29y – 42 = (y + 2) (y – 7)(y + 3)

Question 13. Using factor theorem, factorize of the polynomials : 2y3 – 5y2 – 19y + 42

Solution:

Given that, f(x) = 2y3 – 5y2 – 19y + 42

The constant in f(x) is + 42,

The factors of 42 are ± 1, ± 2, ± 3, ± 6, ± 7, ± 14, ± 21,± 42,

Let’s assume, y – 2 = 0

y = 2

f(2) = 2(2)3 – 5(2)2 – 19(2) + 42

16 – 20 – 38 + 42 = 0



therefore, (y – 2) is the factor of f(y)

Now, divide f(y) with (y – 2) to get other factors

By using long division method we get,

2y3 – 5y2 – 19y + 42 = (y – 2) (2y2 – y – 21)

Now,

2y2 – y – 21

The factors are (y + 3) (2y – 7)

Hence, 2y3 – 5y2 -19y + 42 = (y – 2) (y + 3) (2y – 7)

Question 14. Using factor theorem, factorize of the polynomials : x3 + 13x2 + 32x + 20

Solution:

Given that, f(x) = x3 + 13x2 + 32x + 20

The constant in f(x) is 20,

The factors of 20 are ± 1, ± 2, ± 4, ± 5, ± 10, ± 20,

Let’s assume, x + 1 = 0

x = -1

f(-1) =  (−1)3+13(−1)2 + 32(−1) + 20

-1 + 13 – 32 + 20 = 0

therefore, (x + 1) is the factor of f(x)

Divide f(x) with (x + 1) to get other factors

By using long division method we get,

x3 + 13x2 +32x + 20 = (x + 1)( x2 + 12x + 20)

Now,

x2 + 12x + 20 = x2 + 10x + 2x + 20

x(x + 10) + 2(x + 10)

The factors are (x + 10) and (x + 2)

Hence, x3 + 13x2 + 32x + 20 = (x + 1)(x + 10)(x + 2)

Question 15. Using factor theorem, factorize of the polynomials : x3 – 3x2 – 9x – 5

Solution:

Given that, f(x) = x3 – 3x2 – 9x – 5

The constant in f(x) is -5,

The factors of -5 are ±1, ±5,

Let’s assume, x + 1 = 0



x = -1

f(-1) = (−1)3 – 3(−1)2 – 9(-1) – 5

-1 – 3 + 9 – 5 = 0

therefore, (x + 1) is the factor of f(x)

Divide f(x) with (x + 1) to get other factors

By using long division method we get,

x3 – 3x2 – 9x – 5 = (x + 1)( x2 – 4x – 5)

Now,

x2 – 4x – 5 = x2 – 5x + x – 5

x(x – 5) + 1(x – 5)

The factors are (x – 5) and (x + 1)

Hence, x3 – 3x2 – 9x – 5 = (x + 1)(x – 5)(x + 1)

Question 16. Using factor theorem, factorize of the polynomials : 2y3 + y2 – 2y – 1

Solution:

Given that, f(y) = 2y3 + y2 – 2y – 1

The constant term is 2,

The factors of 2 are ± 1, ± 1/2,

Let’s assume, y – 1= 0

y = 1

f(1) = 2(1)3 +(1)2 – 2(1) – 1

2 + 1 – 2 – 1 = 0

therefore, (y – 1) is the factor of f(y)

Divide f(y) with (y – 1) to get other factors

By using long division method we get,

2y3 + y2 – 2y – 1 = (y – 1) (2y2 + 3y + 1)

Now,

2y2 + 3y + 1 = 2y2 + 2y + y + 1

2y(y + 1) + 1(y + 1)

(2y + 1) (y + 1) are the factors

Hence, 2y3 + y2 – 2y – 1 = (y – 1) (2y + 1) (y + 1)

Question 17. Using factor theorem, factorize of the polynomials : x3 – 2x2 – x + 2

Solution:



Given that, f(x) = x3 – 2x2 – x + 2

The constant term is 2,

The factors of 2 are ±1, ± 1/2,

Let’s assume, x – 1= 0

x = 1

f(1) = (1)3 – 2(1)2 – (1) + 2

1 – 2 – 1 + 2 = 0

therefore, (x – 1) is the factor of f(x)

Divide f(x) with (x – 1) to get other factors

By using long division method we get,

x3 – 2x2 – y + 2 = (x – 1) (x2 – x – 2)

Now,

x2 – x – 2 = x2 – 2x + x  – 2

x(x – 2) + 1(x – 2)

(x – 2)(x + 1)  are the factors

Hence, x3 – 2x2 – y + 2 = (x – 1)(x + 1)(x – 2)

Question 18. Factorize each of the following polynomials :

1. x3 + 13x2 + 31x – 45 given that x + 9 is a factor

2. 4x3 + 20x2 + 33x + 18 given that 2x + 3 is a factor

Solution:

1. x3 + 13x2 + 31x – 45

Given that, x + 9 is a factor

Let’s assume, f(x) = x3 + 13x2 + 31x – 45

divide f(x) with (x + 9) to get other factors

By using long division method we get,

x3 + 13x2 + 31x – 45 = (x + 9)( x2 + 4x – 5)

Now,

x2 + 4x – 5 = x2 + 5x – x  – 5

x(x + 5) -1(x + 5)

(x + 5) (x – 1) are the factors

Hence, x3 + 13x2 + 31x – 45 = (x + 9)(x + 5)(x – 1)

2. 4x3 + 20x2 + 33x + 18 

Given that, 2x + 3 is a factor

let’s assume, f(x) =  4x3 + 20x2 + 33x + 18

divide f(x) with (2x + 3) to get other factors

By using long division method we get,

4x3 + 20x2 + 33x + 18 = (2x + 3) (2×2 + 7x + 6)

Now,

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6

2x(x + 2) + 3(x + 2)

(2x + 3)(x + 2) are the factors

Hence, 4x3 + 20x2 + 33x + 18 = (2x + 3)(2x + 3)(x + 2)

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.




My Personal Notes arrow_drop_up
Recommended Articles
Page :